Determinants of the WTI-Brent price spread revisited - Jerome Geyer-Klingeberg; Andreas W. Rathgeber (Journal of Futures Markets, 2021)
Using autoregressive distributed lag modeling and structural break testing, we explore the drivers of the oil price spread between West Texas Intermediate and Brent in a data set from 1995 to 2019. We find a major structural break in December 2010 and minor breaks in 2005 and 2012. Important spread determinants are the convenience yield, as a proxy for crude oil inventories, the trading activity in crude oil paper markets, shipping costs, as well as the stock market development in the United States and Europe. After the break in 2010, the paper market activity, open interest, and shipping costs have become more important spread drivers.
Keywords: 330; Brent; convenience yield; crude oil; structural break; West Texas Intermediate